Pengaruh Senam Persadia Seri 1 Terhadap Pengeluaran Energi Dan Heart Rate Selama Latihan - Zalillah, Shery Iris (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2019)
This study aims to explain the series 1 persadia gymnastics which can influence the total expiratory energy and pulse associated with exercises to oppose it. It is understood that DM is accessed from energy and pulse pulses during Persadian exercise. Methods: using a study design group pretest and postest control groove design with as many as 24 subjects and given series 1 gymnastics as preparation and series 6 diabetes exercise as a control once for 30-35 minutes. Results: Indonesian diabetes exercise can produce an average energy of 83.77 kcal and deny the pulse which reaches an average of 64.3489, Series 1 Persadia Gymnastics can produce an average energy of 520.33333 kcal and deny the pulse that gets an average an average of 81.1689, and there was a significant increase because (p = 0,000) Conclusion: energy expenditure and pulse during conducting series 1 persadian exercise were in accordance with contributions made by the American Diabetes Association..